Assessment of vitamin D nutritional status among adults in Lu'an, China, based on serum 25-hydroxyvitamin D measured by LC-MS/MS - Liu, Can; Zhan, Xianlin; Qin, Baolei; Sun, Lei; Zhai, Rongrong (Frontiers in Nutrition, 2026)
BackgroundVitamin D deficiency is a global public health concern, yet data from central China—particularly from Lu'an, a city located within the Dabie Mountain area—remain limited.ObjectivesThis study aimed to evaluate vitamin D nutritional status in adults from Lu'an, China, based on serum 25-hydroxyvitamin D [25(OH)D] measured by liquid chromatography-tandem mass spectrometry (LC-MS/MS), and to assess variations by sex, age, season, and the relative contributions of 25(OH)D2 and 25(OH)D3.MethodsSerum samples from 380 adults undergoing health examinations between October 2023 and May 2025 were analyzed. Nutritional status categories and subgroup differences were compared using nonparametric methods, with stratified comparisons by sex, age, season, and body mass index.ResultsThe median serum 25(OH)D level was 21.60 ng/ml, with 11.05% of subjects being vitamin D deficient and 31.05% insufficient. Women had significantly lower vitamin D levels than men (P = 0.042), with higher deficiency and insufficiency rates (P < 0.001; P = 0.035). Although no significant differences were found in overall levels among age groups, the deficiency rate was significantly higher in young adults than in the elderly group (P = 0.043). Seasonal analysis showed the lowest 25(OH)D levels in winter (median 18.66 ng/ml) and the highest in summer (median 24.31 ng/ml). Overweight participants had lower 25(OH)D levels and higher insufficiency rates than those with normal weight. Lower serum 25(OH)D levels were observed in women, during winter, and among overweight individuals. Seasonal variation was pronounced, with the lowest levels in winter and the highest in summer. 25(OH)D3 was the predominant form, accounting for 98.5% of total 25(OH)D, while 25(OH)D2 contributed only 1.5% on average.ConclusionsVitamin D insufficiency is common among adults in Lu'an, especially in women, younger individuals, during winter, and among overweight individuals. Given the predominance of vitamin D3, supplementation strategies should prioritize D3 and be tailored to demographic, seasonal, and BMI-related high-risk subgroups, providing evidence for targeted public health interventions among adults in Lu'an.